2011
DOI: 10.2136/sssaj2010.0257
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Properties and the Water-Conducting Porosity as Affected by Subsurface Compaction using Tension Infiltrometers

Abstract: Changes in soil physical properties due to compaction are a major concern in agricultural production and modeling of soil water movement and plant growth. The objectives of this study were to measure water infiltration under different compaction levels and to characterize the effects of compaction on the soil's porosity and its associated water-conducting properties. On a silt loam soil, relative to a control, four levels of subsurface compaction were induced: loosening and light, medium, and heavy compaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…As observed by Schwen et al (2011a, b) in a similar experiment, tillage operations had not a significant influence on n. This behavior could be due to the fact that the n parameter is more related to the soil texture (Jirku et al, 2013), while θ s and α are more associated to the soil structure. This hypothesis agrees with Schwen et al (2011c), who found that α was significantly affected by soil compaction. The increase of PSD max due to tillage operations (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…As observed by Schwen et al (2011a, b) in a similar experiment, tillage operations had not a significant influence on n. This behavior could be due to the fact that the n parameter is more related to the soil texture (Jirku et al, 2013), while θ s and α are more associated to the soil structure. This hypothesis agrees with Schwen et al (2011c), who found that α was significantly affected by soil compaction. The increase of PSD max due to tillage operations (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Analyses of h and r data showed that the average proportion of soil pores under the arable system can be grouped as 35, 28, and 37 % for transmission, storage, and residual pores, respectively; whereas for soils under the fallow system, these averages are 9, 18, and 73 % respectively. These results further reflect the comparative values of plant available water θ PAW , (i.e., storage pores) of both land management systems ( Figure 1d); and such changes in pore configuration place further restrictions on hydraulically effective (fluid conductivity) pores in fallow system soils (Kutílek, 2004;Schwen et al, 2011).…”
Section: Pore Size Distribution Via Spline Functionsupporting
confidence: 66%
“…Land-management induced changes in PSDs demonstrate the ability of soil pores to hold water (Schwen et al, 2011). The change in porosity can be better appreciated when we look at pore size in a functional manner.…”
Section: Pore Size Distribution Via Spline Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies suggest an increase of K(h) for clayey tilled soils shortly after tillage followed by a considerable decrease during winter and, finally, by an increase during spring/summer due to enhanced soil macroporosity (i.e., cracks, root development, earthworms channels) (Messing and Jarvis, 1993). These studies allowed identifying the key factors involved in the general temporal dynamics of K(h), such as initial soil water content (e.g., Das Gupta et al, 2006Zhou et al, 2008, porosity network (e.g., Buczko et al, 2006;Schwen et al, 2011b), crusting (e.g., Vandervaere et al, 1997Vandervaere et al, , 1998, crop and cropping periods (e.g., Castellini and Ventrella, 2012;Rienzner and Gandolfi, 2014) and tillage treatments (e.g., conventional tillage, reduced tillage, no-till) (e.g., Daraghmeh et al, 2008;Fuentes et al, 2004). However, less attention has been paid to the assessment of vertical variability compared to horizontal variability (Schwen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%